Generation of Cyclic ADP-ribose and Nicotinic Acid Adenine Dinucleotide Phosphate by CD38 for Ca(2+) Signaling in Interleukin-8-treated Lymphokine-activated Killer Cells - Rah, So-Young (American Society for Biochemistry and Molecular Biology, 2010)
We have previously demonstrated that cyclic ADP-ribose (cADPR) is a calcium signaling messenger in interleukin 8 (IL-8)-induced lymphokine-activated killer (LAK) cells. In this study we examined the possibility that IL-8 activates CD38 to produce another messenger, nicotinic acid adenine dinucleotide phosphate (NAADP), in LAK cells, and we showed that IL-8 induced NAADP formation after cADPR production. These calcium signaling messengers were not produced when LAK cells prepared from CD38 knock-out mice were treated with IL-8, indicating that the synthesis of both NAADP and cADPR is catalyzed by CD38 in LAK cells. Application of cADPR to LAK cells induced NAADP production, whereas NAADP failed to increase intracellular cADPR levels, confirming that the production of cADPR precedes that of NAADP in IL-8-treated LAK cells. Moreover, NAADP increased intracellular Ca(2+) signaling as well as cell migration, which was completely blocked by bafilomycin A1, suggesting that NAADP is generated in lysosome-related organelles after cADPR production. IL-8 or exogenous cADPR, but not NAADP, increased intracellular cAMP levels. cGMP analog, 8-(4-chlorophenylthio)-guanosine 3′,5′-cyclic monophosphate, increased both cADPR and NAADP production, whereas the cAMP analog, 8-(4-chlorophenylthio)-cAMP, increased only NAADP production, suggesting that cAMP is essential for IL-8-induced NAADP formation. Furthermore, activation of Rap1, a downstream molecule of Epac, was required for IL-8-induced NAADP formation in LAK cells. Taken together, our data suggest that IL-8-induced NAADP production is mediated by CD38 activation through the actions of cAMP/Epac/protein kinase A/Rap1 in LAK cells and that NAADP plays a key role in Ca(2+) signaling of IL-8-induced LAK cell migration.